2020
DOI: 10.1038/s41467-020-19095-z
|View full text |Cite
|
Sign up to set email alerts
|

Metformin enhances anti-mycobacterial responses by educating CD8+ T-cell immunometabolic circuits

Abstract: Patients with type 2 diabetes (T2D) have a lower risk of Mycobacterium tuberculosis infection, progression from infection to tuberculosis (TB) disease, TB morality and TB recurrence, when being treated with metformin. However, a detailed mechanistic understanding of these protective effects is lacking. Here, we use mass cytometry to show that metformin treatment expands a population of memory-like antigen-inexperienced CD8+CXCR3+ T cells in naive mice, and in healthy individuals and patients with T2D. Metformi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 73 publications
3
41
0
Order By: Relevance
“…A beneficial effect of metformin on in vivo Mtb clearance was also shown by Bohme et al In Mtb-infected mice that received metformin along with pyrazinamide and isoniazid for 30 days, bacterial burden was compared to mice having received only pyrazinamide and isoniazid [83] confirming that metformin can enhance the sterilizing activity of available antimicrobial treatment for Mtb infection. Conducting subsequent mechanistic experiments, the authors revealed that metformin enhances the host immune function against Mtb via reprograming CD8(+) T cell metabolism, favoring in the expansion of memory CD8+CXCR3+ T cells population with anti-Mtb properties.…”
Section: Metforminsupporting
confidence: 59%
“…A beneficial effect of metformin on in vivo Mtb clearance was also shown by Bohme et al In Mtb-infected mice that received metformin along with pyrazinamide and isoniazid for 30 days, bacterial burden was compared to mice having received only pyrazinamide and isoniazid [83] confirming that metformin can enhance the sterilizing activity of available antimicrobial treatment for Mtb infection. Conducting subsequent mechanistic experiments, the authors revealed that metformin enhances the host immune function against Mtb via reprograming CD8(+) T cell metabolism, favoring in the expansion of memory CD8+CXCR3+ T cells population with anti-Mtb properties.…”
Section: Metforminsupporting
confidence: 59%
“…Many HDT candidates target these pathways. For example, metformin mediates the AKT-mTOR pathway, blunting cellular glycolysis and the TCA cycle leading to inhibition of chromatin conformational changes that ultimately drive antigen-induced immune function(46, 47, 50). These data suggest that attempts to modulate metabolic and immune mechanisms should be applied in an endotype-specific manner.…”
Section: Discussionmentioning
confidence: 99%
“…It is also demonstrated that prolonging boosting intervals can induce a stronger booster response and enhanced long-term protective efficacy against M. tuberculosis [ 28 , 33 ]. Metformin could expand memory-like antigen-inexperienced CD8 + T cells and enhance protective efficacy against M. tuberculosis challenge [ 34 ]. Some studies have demonstrated that IL-7 and IL-15 can promote formation and homeostasis of memory T cells [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%